Software engineering and 12 prominent sub‐areas: Comprehensive bibliometric assessment on 13 years (2007–2019) - Sana Alam; Shehnila Zardari; Muneera Bano (IET Software)
Abstract Software Engineering (SE) as a field has grown significantly in terms of the research publications in the last few years. Criterion‐based assessment of research performance of scholars, countries along with collaboration networks and links among articles are better judged using bibliometric analysis. The results proposed in this work are based on quantitative analysis and data visualisation of 150,087 scholarly articles published in last 13 years (2007–2019) across 85 research areas based on seven categories by providing a detailed and distinctive time‐frame‐based comparison to observe a shift in research trend in SE and its 12 distinguished sub‐areas. The results of the observations proposed in this work include analysis on types of documents, yearly publication trends with results suggesting a prominent increment for the period (2015–2017) in terms of research publications, languages of research publications with findings indicating that there are articles published in languages other than English language, also, publication count‐based rankings of authors, collaboration networks of countries with findings showing the supremacy of USA and China and keyword statistics.